Respon Pertumbuhan Bibit Tebu (Saccharum Officinarum L.) Pada Aplikasi Biostimulan Dari Ekstrak Bawang Merah - Zaroh, Nadya Shinta; Asmono, Sepdian Luri (Jurnal Penelitian Pertanian Terapan, 2023)
Sugarcane (Saccharum officinarum L.) is a plantation commodity that has an important role in the economy in Indonesia. The demand for sugar increases with the increase in population. Therefore efforts to increase sugar production by increasing the productivity of sugarcane, one of which is through the use of high quality seeds. Sugarcane Bud Chip seeds have the potential to produce sugarcane with high yields, but efforts to stimulate seedling growth really need to be increased. The use of Biostimulant from shallot extract needs to be tested on sugarcane seedlings because shallots contain the hormone auxin and vitamin B1 which are very necessary to increase the growth of sugarcane seedlings. Therefore this study aims to determine the effect of shallot extract concentration on the initial growth of sugarcane plants using the bud chip method and determine the best concentration. This study was conducted for 2.5 months and was designed using a non-factorial randomized block design with 5 concentrations of shallot extract including B0 (control/no extract); B1 (20%); B2 (40%); B3 (60%); B4 (80%). The parameters include the number of tillers, plant height, number of leaves, and root length. The results of this study indicated that the shallot extract gave a significantly different response to the growth of sugar cane seedlings, as seen in the parameters of the number of tillers, the number of leaves and root length. From the data obtained, shallot extract at a concentration of 40% was the best concentration for all parameters.